Chronostratigraphy of two Late Pleistocene loess-palaeosol sequences in the Rhône Valley (southeast France). (1st October 2020) - Bosq, Mathieu; Kreutzer, Sebastian; Bertran, Pascal; Degeai, Jean-Philippe; Dugas, Pauline; Kadereit, Annette; Lanos, Philippe; Moine, Olivier; Pfaffner, Nora; Queffelec, Alain; Sauer, Daniela
Abstract: A sedimentological and chronostratigraphical investigation was carried out on two loess sections located in the Mediterranean area in southeast France along the Rhône River (Lautagne) and the lower reach of a tributary of the Rhône River (Collias). High-resolution sampling (5–20 cm) for magnetic susceptibility, grain size distribution (including non-parametric end-member modelling), colour reflectance and geochemistry was performed. The chronology was based on luminescence dating of quartz grains and radiocarbon dating of small gastropod shells, coupled with hierarchical Bayesian modelling. The Collias section (∼8 m thick) records the whole last climatic cycle. It comprises a thick red basal pedocomplex S1 developed during the Last Interglacial and the Early Glacial, similar to that observed elsewhere in southern and southeastern Europe. Loess deposition occurred during the Lower (L1L2) and the Upper Pleniglacial (L1L1). It was interrupted by soil formation during the Middle Pleniglacial, of which a brown Bwk horizon has been preserved (L1S1). By contrast, the ∼5 m thick Lautagne section provides a detailed record of the Upper Pleniglacial. Weakly developed hydromorphic soils are correlated with the Greenland Interstadials GI-4 to GI-2, while the main period of coarse loess sedimentation corresponds to the Greenland Stadials GS-5 to GS-2. At a regional scale, the time of loess deposition ranges between 38.5 ka and 12 ka, with a peak at ∼28–24 ka, overlapping with the maximal advance of the Alpine Ice Sheet (AIS). This strongly suggests that regional glacier dynamics was the main driver of loess sedimentation. Highlights: Two high-resolution loess-palaeosol records in the Rhône Valley, southeast France. The Collias section exhibits a remarkable (8 m) Last Glacial loess accumulation. The Lautagne section provides a detailed record of the Upper Pleniglacial. The main period of loess deposition ranges between 28 ka and 24 ka. The maximum dust accumulation coincides with the maximal advance of the Alpine glaciers.